Building Kenya Social Accounting Matrices (SAMs) - International Food Policy Research Institute (CGIAR System Organization, 2022)
International Food Policy Research Institute (IFPRI) kicked off a six-day workshop on September 19, 2022 in Nakuru, Kenya. The workshop aimed to share capacity on Social Accounting Matrices (SAMs), and the standardized toolkit for building SAM. This forms part of Kenya’s Capacity Sharing Workshops Series under the CGIAR Initiatives on National Policies and Strategies (NPS), and Foresight.